Biomass-based aqueous binder for silicon negative electrode of lithium ion battery as well as preparation method and application of biomass-based aqueous binder
By using biomass-based water-based binder in the silicon negative electrode of lithium-ion batteries, the structural damage and environmental pollution caused by traditional binders during volume expansion are solved, and the high circulation performance and green environmental protection effect is achieved.
Patent Information
- Application Number
- CN202411584054.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-07
AI Technical Summary
During the charging and discharging process, the silicon anode material of traditional lithium-ion batteries causes structural damage and material collapse and fall off due to volume expansion, affecting the battery performance and service life. At the same time, the commonly used adhesives require organic solvents, which poses environmental pollution and safety problems.
A high elastic biomass-based water-based binder was used to form a CMC-PCA binder under the action of hydrogen peroxide/ferrous sulfate through carboxymethylcellulose (CMC) and caffeic acid (CA), and the pH value was adjusted by LiOH to prepare a high elastic biomass-based water-based binder for the silicon negative electrode of lithium-ion batteries.
The binder significantly improves the circulation performance and capacity retention rate of the silicon negative electrode of lithium-ion battery at a lower content, avoids structural damage caused by volume expansion, and has no environmental pollution problems due to the use of water as a solvent, which is in line with the concept of green development.
Smart Images

Figure CN119592257A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of synthesis of lithium ion battery electrode materials and biomass binders, and in particular to a biomass-based aqueous binder for lithium ion battery silicon negative electrode, and a preparation method and application thereof. Background Art
[0002] The negative electrode of traditional lithium-ion batteries is generally graphite, which has a low theoretical specific capacity and cannot meet people's increasing requirements for the energy storage density of lithium-ion batteries.
[0003] Compared with graphite anode, the theoretical specific capacity of silicon anode is more than ten times that of commercial graphite electrode. However, silicon-based materials will undergo drastic volume changes (>400%) during the insertion and extraction of lithium ions. On the one hand, the commonly used electrode material binders such as polyvinylidene fluoride (PVDF) and styrene-butadiene rubber (SBR) have poor stability in repeated deformation and are difficult to inhibit the volume expansion of silicon-based anode, which leads to the destruction of electrode structure, the collapse and shedding of materials, and then causes the decline and failure of battery performance, seriously affecting the service life of the battery; on the other hand, the dissolution of these commonly used binders requires the use of organic solvents such as N-methylpyrrolidone (NMP), which poses environmental pollution and safety issues and is not in line with the concept of green development.
[0004] Therefore, it is necessary to develop a highly elastic aqueous binder with strong bonding properties and mechanical strength that can be applied to silicon negative electrodes to prevent or reduce the breakage and peeling of silicon negative electrode materials during charging and discharging, buffer the deformation stress caused by volume expansion, and reduce the use of organic solvents. Summary of the invention
[0005] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing a biomass-based aqueous binder for a silicon negative electrode of a lithium ion battery.
[0006] Another object of the present invention is to provide a biomass-based aqueous binder for lithium-ion battery silicon negative electrode prepared by the method.
[0007] Another object of the present invention is to provide an application of the biomass-based aqueous binder for lithium-ion battery silicon negative electrode.
[0008] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a biomass-based aqueous binder for a lithium-ion battery silicon negative electrode comprises the following steps: (1) Add carboxymethyl cellulose (CMC) to water, heat and stir to mix evenly to obtain a colloidal solution; (2) adding caffeic acid (CA) to the colloidal solution obtained in step (1), heating and stirring to mix evenly, to obtain a mixed solution; (3) Hydrogen peroxide (H 2 O 2 ) and ferrous sulfate (FeSO 4 ) is added to the mixed solution obtained in step (2), heated and stirred for reaction (to complete the reaction), to obtain a CMC-PCA colloidal solution; (4) Adding LiOH solution to the CMC-PCA colloidal solution obtained in step (3) to adjust the pH value to 6-8, thereby obtaining the biomass-based aqueous binder for the silicon negative electrode of lithium ion battery.
[0009] The water described in step (1) is preferably deionized water.
[0010] The mass ratio of carboxymethyl cellulose (CMC) to water in step (1) is (0.02-0.05):1; preferably 0.04:1.
[0011] The mass ratio of the carboxymethyl cellulose (CMC) to the caffeic acid (CA) in step (1) is 1:(0.05-0.15): preferably 1:0.1.
[0012] In steps (1), (2) and (3), a magnetic stirrer is used for heating and stirring.
[0013] The temperature of the heating and stirring in steps (1), (2) and (3) is 55-60°C, preferably 55°C.
[0014] The rotation speed of the heating and stirring in steps (1), (2) and (3) is 250 to 300 rpm, preferably 250 rpm.
[0015] The heating and stirring time in steps (1) and (2) is 20 to 30 min, preferably 30 min.
[0016] The hydrogen peroxide (H 2 O 2 ) and ferrous sulfate (FeSO 4 ) is (0.1-0.2):1; preferably 0.1:1.
[0017] The hydrogen peroxide (H 2 O 2 The mass ratio of ) to the caffeic acid (CA) is 1:(100-150); preferably 1:100.
[0018] The heating and stirring reaction time in step (3) is 1.5 to 2 h, preferably 1.5 h.
[0019] The concentration of the LiOH solution in step (4) is 20% to 30% by mass, preferably 30% by mass.
[0020] The pH value adjusted in step (4) is preferably adjusted to a value between 6 and 7.
[0021] A biomass-based aqueous binder for a lithium-ion battery silicon negative electrode is prepared by any of the methods described above.
[0022] The biomass-based aqueous binder for lithium-ion battery silicon negative electrode is used in the preparation of lithium-ion battery negative electrode materials or lithium-ion batteries.
[0023] The negative electrode material of the lithium-ion battery is a lithium-ion battery silicon negative electrode material.
[0024] A negative electrode material for a lithium ion battery comprises active material silicon, a conductive agent and the above-mentioned biomass-based aqueous binder for the silicon negative electrode of a lithium ion battery.
[0025] The active material silicon is preferably silicon powder; more preferably silicon powder with a particle size of about 100 nm.
[0026] The conductive agent can be selected according to actual needs; preferably, it is carbon black; more preferably, it is carbon black with a particle size of about 100 nm.
[0027] In the lithium-ion battery negative electrode material, the amount of the biomass-based aqueous binder used for the lithium-ion battery silicon negative electrode accounts for 5-10% of the mass of the lithium-ion battery negative electrode material.
[0028] The method for preparing the negative electrode material for a lithium-ion battery comprises mixing and stirring the active material silicon, the conductive agent and the above-mentioned biomass-based aqueous binder for the silicon negative electrode of a lithium-ion battery uniformly to obtain a uniformly dispersed electrode slurry; then coating the electrode slurry on a copper foil, drying, rolling with a roller press, and cutting to obtain an electrode disc, i.e., the negative electrode material for a lithium-ion battery.
[0029] The mass ratio of the active material silicon, the conductive agent and the biomass-based aqueous binder for the silicon negative electrode of the lithium ion battery is (7-8.5): (1-2): (0.5-1); preferably 8:1:1.
[0030] The stirring time is 5 to 6 h, preferably 6 h.
[0031] The drying conditions are: vacuum drying at 60±5°C for 12 to 15 h; preferably: vacuum drying at 60°C for 12 h.
[0032] The thickness of the negative electrode material of the lithium-ion battery is 3 to 5 μm.
[0033] A lithium-ion battery comprises a positive electrode material, the above-mentioned negative electrode material of the lithium-ion battery, a separator and an electrolyte.
[0034] The lithium-ion battery is preferably a CR2032 button battery (if a half-battery is to be made, a lithium sheet can be used as a counter electrode).
[0035] The positive electrode material is preferably LiFePO 4 .
[0036] The separator is preferably a commercial PE film.
[0037] The electrolyte is preferably LiPF 6 solution; more preferably a LiPF solution having a concentration of 1 mol / L 6 Solution.
[0038] The caffeic acid used in the present invention contains a catechol group, a carboxylic acid group, and a carbon-carbon double bond. 2 O 2 / FeSO 4 ) initiates polymerization to form a CMC-PCA binder. On the one hand, the caffeic acid monomer forms ester bonds and hydrogen bonds with the CMC network, and the carboxylic acid groups and hydroxyl groups of the two can also form stable ester bonds and hydrogen bonds with the Si surface oxidation groups, which reflects the binder's ability to bind active materials; on the other hand, the caffeic acid monomer self-polymerizes and cross-links with the CMC network, making the binder mechanically stronger, and the catechol groups can achieve adhesion through chemical actions such as hydrogen bonds, metal chelation coordination, π-π stacking, and covalent bonding. The composite binder can be used to enhance the cycle performance and capacity retention rate of silicon-based negative electrodes of lithium-ion batteries. The silicon-based negative electrode using the composite binder can maintain good cycle performance and capacity retention rate under the condition of low binder content (5-10 wt%).
[0039] Compared with the prior art, the present invention has the following advantages and effects: (1) The present invention aims to solve the problems of weak bonding ability, poor mechanical strength and serious environmental pollution of traditional binders, and provides a method for preparing a highly elastic biomass-based water-based binder for use in silicon negative electrodes of lithium-ion batteries. Carboxymethyl cellulose (CMC) and caffeic acid (CA) are used as raw materials. Under the action of initiator hydrogen peroxide / ferrous sulfate, polymerization is rapidly initiated to form a CMC-PCA binder. Finally, LiOH is used to neutralize the binder to enhance the viscosity of the binder and the Li + Conductivity efficiency. Due to the combined effect of the binder's network structure and the mussel-like structure, its mechanical strength and bonding ability with the active material and the current collector are extremely excellent.
[0040] (2) The main raw materials used in the present invention come from plants, which are abundant in source, highly safe, renewable and degradable. The solvent is water, which is pollution-free to the environment, green and environmentally friendly, and has the potential for large-scale commercial application.
[0041] (3) The highly elastic biomass-based aqueous binder of the present invention is polymerized under the action of an initiator. Due to the network structure of the CMC binder and the chemical action of the catechol group of the caffeic acid monomer on CMC, Si particles, and current collector metal, the composite binder has excellent adhesive strength and mechanical properties.
[0042] (4) The highly elastic biomass-based aqueous binder of the present invention is applied to the silicon negative electrode of lithium-ion batteries, which effectively enhances its cycle performance and capacity retention rate. The cycle performance of the silicon negative electrode was tested by comparing the binder CMC-PCA of the present invention with PVDF, CMC and a simple blended CMC-CA binder. Under 1 C constant current charge and discharge, the first discharge specific capacity of the CMC-PCA prepared by the present invention is 3868 mAh·g -1 The first coulombic efficiency is 92.09%. After 100 cycles, the discharge capacity remains at 2476 mAh g -1 The capacity retention rate is 64.01%; the first discharge specific capacity of PVDF is 3000 mAh·g -1 The first coulombic efficiency is 71.43%. After 20 cycles, there is basically no discharge capacity. The first discharge capacity of CMC is 3525 mAh g -1 The first coulombic efficiency is 83.93%. After 100 cycles, the discharge capacity is only 1722 mAh g -1 The capacity retention rate is 48.85%; the first discharge capacity of the simply blended CMC-CA is 3214 mAh·g -1 The first coulombic efficiency is 76.52%. After 100 cycles, the discharge capacity is only 1320 mAh g -1 The capacity retention rate is 41.07%, which indicates that after the binder of the present invention is applied to the silicon negative electrode of the lithium ion battery, the performance of the battery can be significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a cycle performance diagram of a full battery assembled with a silicon negative electrode prepared using the highly elastic biomass-based aqueous adhesive in Example 1, the PVDF binder in Comparative Example 1, and the CMC binder in Comparative Example 2 at 1 C. DETAILED DESCRIPTION
[0044] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. The battery electrochemical performance detection methods in the following examples are all general detection methods for the electrochemical performance of lithium ion batteries. The raw materials and reagents used in the following examples, unless otherwise specified, can all be obtained from commercial sources.
[0045] In the present invention, unless otherwise specified, all percentages (%) are mass percentages.
[0046] The carboxymethyl cellulose (CMC) powder and caffeic acid (CA) involved in the examples and comparative examples of the present invention are analytically pure; the effective content of ferrous sulfate is not less than 90%; the particle size of silicon powder is 100 nm, and the effective content is not less than 99.99%; the particle size of carbon black is 100 nm, and the effective content is not less than 99.5%. The above raw materials and reagents are purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0047] The effective content of hydrogen peroxide involved in the examples and comparative examples of the present invention is not less than 99.99%, which is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; the effective content of lithium hydroxide (LiOH) is not less than 99.9%, which is purchased from Shanghai Bangcheng Chemical Co., Ltd.
[0048] The embodiments and comparative examples of the present invention are all based on LiFePO 4 As the positive electrode, commercial PE film is used as the separator, and the electrolyte is 1 MLiPF 6 The solution was assembled into a full battery (CR2032 button battery) for cycle performance testing. The above battery materials are all commercial products purchased from Clude New Energy Technology Co., Ltd.
[0049] Example 1 (1) Place 24 g of deionized water in a 50 mL pressure bottle; (2) Add 1 g of carboxymethyl cellulose (CMC) powder into the pressure bottle in step (1), stir at 55°C and 250 rpm for 30 min to obtain a colloidal solution with a certain viscosity; (3) Add 0.1 g of caffeic acid monomer (CA) to the colloidal solution prepared in step (2), and continue stirring at 55°C and 250 rpm for 30 min to obtain a mixed solution with a certain viscosity; (4) 0.001 g of hydrogen peroxide and 0.01 g of ferrous sulfate were added to the mixed solution prepared in step (3) in sequence, and the mixture was stirred at 55° C. and 250 rpm for 1.5 h to obtain a CMC-PCA colloidal solution with a certain viscosity; (5) slowly adding a 30% by mass concentration LiOH solution to the colloidal solution prepared in step (4) to adjust the pH to 6-7, thereby obtaining the highly elastic biomass-based aqueous binder for silicon negative electrode; (6) The active material Si (silicon powder), the conductive agent carbon black and the binder prepared in step (5) in a mass ratio of 8:1:1 were mixed and stirred for 6 h to obtain a uniformly dispersed electrode slurry. The obtained slurry was coated on a copper foil using a doctor blade coater, dried in a vacuum drying oven at 60°C for 12 h, taken out, rolled to 3 µm using a roller press, and cut into electrode discs with a diameter of 12 mm.
[0050] (7) The electrode disc (as the negative electrode) dried in step (6) was transferred to a glove box filled with argon gas for battery assembly. 4 The electrode was used as the positive electrode and the electrolyte was 1 M LiPF 6 The solution was a commercial PE film as the separator, and CR2032 button cells were used for assembly to prepare full batteries for cycle performance testing.
[0051] Example 2 The difference from Example 1 is that the mass of the caffeic acid monomer added in step (3) is adjusted to 0.05 g, and the other step parameters are the same as those in Example 1.
[0052] Example 3 The difference from Example 1 is that the mass of the caffeic acid monomer added in the adjustment step (3) is 0.15 g, and the other step parameters are the same as those in Example 1.
[0053] Comparative Example 1 (1) Dissolve 2 g of polyvinylidene fluoride (PVDF) powder in 8 g of N-methylpyrrolidone (NMP) to obtain a PVDF binder with a mass concentration of 20%; (2) The active material Si (silicon powder), the conductive agent carbon black and the PVDF binder prepared in step (1) in a mass ratio of 8:1:1 were mixed and stirred for 6 h to obtain a uniformly dispersed electrode slurry. The obtained slurry was coated on a copper foil using a doctor blade coater, dried in a vacuum drying oven at 60°C for 12 h, taken out, rolled to 3 µm using a roller press, and cut into electrode discs with a diameter of 12 mm.
[0054] (3) The electrode disc (as the negative electrode) dried in step (2) was transferred to a glove box filled with argon gas for battery assembly. 4 The electrode was used as the positive electrode and the electrolyte was 1 M LiPF 6 The solution was a commercial PE film as the separator, and CR2032 button cells were used for assembly to prepare full batteries for cycle performance testing.
[0055] Comparative Example 2 (1) Dissolve 0.4 g of CMC powder in 9.6 g of deionized water to obtain a CMC binder with a mass concentration of 4%; (2) The active material Si (silicon powder), the conductive agent carbon black and the CMC binder prepared in step (1) in a mass ratio of 8:1:1 were mixed and stirred for 6 h to obtain a uniformly dispersed electrode slurry. The obtained slurry was coated on a copper foil using a doctor blade coater, dried in a vacuum drying oven at 60°C for 12 h, taken out, rolled to 3 µm using a roller press, and cut into electrode discs with a diameter of 12 mm.
[0056] (3) The electrode disc (as the negative electrode) dried in step (2) was transferred to a glove box filled with argon gas for battery assembly. 4 The electrode was used as the positive electrode and the electrolyte was 1 M LiPF 6 The solution was a commercial PE film as the separator, and CR2032 button cells were used for assembly to prepare full batteries for cycle performance testing.
[0057] Comparative Example 3 (1) Dissolve 1 g of CMC powder in 24 g of deionized water to obtain a colloidal solution with a certain concentration.
[0058] (2) Dissolve 0.1 g CA directly in the colloidal solution prepared in step (1), heat and stir to mix evenly, and obtain a blended CMC-CA binder.
[0059] (3) The active material Si (silicon powder), the conductive agent carbon black and the CMC-CA binder prepared in step (2) in a mass ratio of 8:1:1 were mixed and stirred for 6 h to obtain a uniformly dispersed electrode slurry. The obtained slurry was coated on a copper foil using a doctor blade coater, dried in a vacuum drying oven at 60°C for 12 h, taken out, rolled to 3 µm using a roller press, and cut into electrode discs with a diameter of 12 mm.
[0060] (3) The electrode disc (as the negative electrode) dried in step (3) is transferred to a glove box filled with argon gas for battery assembly. 4 The electrode was used as the positive electrode, the electrolyte was 1 M LiPF6 solution, the separator was a commercial PE film, and CR2032 button cells were used for assembly to prepare a full battery for cycle performance testing.
[0061] Effect Example 1. The thickness and load of the electrode discs (silicon negative electrodes) prepared in Examples 1-3 and Comparative Examples 1-3 were tested in accordance with GB / T20220-2006. The silicon negative electrodes prepared using different binders in Examples 1-3 and Comparative Examples 1-3 were then assembled into full batteries, and the first charge and discharge and 100 cycle charge and discharge tests of lithium-ion batteries were performed under 1 C constant current charge and discharge; the first discharge capacity and 100 cycle discharge capacity were tested in accordance with GB / T31467.2-2015. The results are shown in Table 1 below.
[0062] Table 1 Performance comparison of various binders in the examples and comparative examples The battery cycling system is used to test the cycling performance of the assembled battery. Figure 1 The cycle performance diagram of the full battery assembled with the high elastic biomass-based aqueous adhesive in Example 1, the PVDF adhesive in Comparative Example 1, and the CMC adhesive in Comparative Example 2 as the adhesive for the Si electrode. It can be seen that the adhesive prepared by the present invention is significantly better than the PVDF adhesive and the CMC adhesive. In addition, when CMC-CA is simply blended (Comparative Example 3), the viscosity of the adhesive will decrease, and the prepared electrode will show obvious shedding and powdering phenomenon, and it can be seen from the data in Table 1 that its first coulomb efficiency and capacity retention rate are also low. It can be seen that when the adhesive of the present invention is applied to the silicon negative electrode of a lithium-ion battery, the performance of the battery is significantly improved.
[0063] 2. The binders prepared in Examples 1-3 and Comparative Examples 1-3 were prepared into films by suction filtration, and their quantitative, tensile strength and elongation were tested, wherein the quantitative was tested according to GB / T451.2-2002, and the tensile strength and elongation were tested according to GB / T12914-2018. The results are shown in Table 2 below.
[0064] Table 2 Comparison of mechanical properties of adhesive films in Examples and Comparative Examples It can be seen from the data in Table 2 that after the adhesives of the embodiments and comparative examples are made into films, the tensile strength and elongation of the CMC-PCA film made from the adhesive of the present invention are significantly improved, reflecting its excellent mechanical properties, namely elasticity.
[0065] In summary, the main raw material of the composite binder of the present invention comes from plants, which are abundant, renewable and degradable, and the solvent is water, which is pollution-free to the environment. The silicon-based negative electrode using the composite binder can maintain good cycle performance and capacity retention rate under the condition of low binder content (5-10wt%), and has great application potential in the application of anti-electrode deformation.
[0066] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a biomass-based aqueous binder for a lithium-ion battery silicon negative electrode, characterized in that: The steps include: (1) Add carboxymethyl cellulose to water, heat and stir to mix evenly to obtain a colloidal solution; (2) adding caffeic acid to the colloidal solution obtained in step (1), heating and stirring to mix evenly, to obtain a mixed solution; (3) adding hydrogen peroxide and ferrous sulfate to the mixed solution obtained in step (2), heating and stirring to react, and obtaining a CMC-PCA colloidal solution; (4) Adding LiOH solution to the CMC-PCA colloidal solution obtained in step (3) to adjust the pH value to 6-8, thereby obtaining the biomass-based aqueous binder for the silicon negative electrode of lithium ion battery.
2. The method according to claim 1, characterized in that: The mass ratio of carboxymethyl cellulose to water in step (1) is 0.02-0.05:1; The mass ratio of the carboxymethyl cellulose to the caffeic acid in step (1) is 1:0.05-0.15; The mass ratio of hydrogen peroxide to ferrous sulfate in step (3) is 0.1-0.2:1; The mass ratio of the hydrogen peroxide to the caffeic acid in step (3) is 1:100-150.
3. The method according to claim 2, characterized in that: The mass ratio of carboxymethyl cellulose to water in step (1) is 0.04:1; The mass ratio of the carboxymethyl cellulose to the caffeic acid in step (1) is 1:0.1; The mass ratio of hydrogen peroxide to ferrous sulfate in step (3) is 0.1:1; The mass ratio of the hydrogen peroxide to the caffeic acid in step (3) is 1:
100.
4. The method according to claim 1, characterized in that: The concentration of the LiOH solution in step (4) is 20% to 30% by mass; The pH value adjusted in step (4) is adjusted to a pH value of 6 to 7.
5. The method according to claim 1, characterized in that: The temperature of the heating and stirring in steps (1), (2) and (3) is 55-60°C; The speed of the heating and stirring in steps (1), (2) and (3) is 250 to 300 rpm; The heating and stirring time in steps (1) and (2) is 20 to 30 minutes; The heating and stirring reaction time in step (3) is 1.5 to 2 h.
6. A biomass-based aqueous binder for lithium-ion battery silicon negative electrode, characterized in that: It is prepared by the method according to any one of claims 1 to 5.
7. Use of the biomass-based aqueous binder for lithium-ion battery silicon negative electrode according to claim 6 in the preparation of lithium-ion battery negative electrode materials or lithium-ion batteries.
8. A negative electrode material for a lithium ion battery, characterized in that: The invention comprises active material silicon, a conductive agent and the biomass-based aqueous binder for lithium-ion battery silicon negative electrode as claimed in claim 6.
9. The negative electrode material for a lithium-ion battery according to claim 8, characterized in that: The active material silicon is silicon powder; The conductive agent is carbon black; The amount of the biomass-based aqueous binder used for the lithium-ion battery silicon negative electrode accounts for 5-10% of the mass of the lithium-ion battery negative electrode material.
10. A lithium ion battery, characterized in that: Comprising a positive electrode material, a negative electrode material for a lithium-ion battery according to claim 8 or 9, a separator and an electrolyte; The positive electrode material is LiFePO4; The diaphragm is a PE film; The electrolyte is LiPF6 solution.
Citation Information
Patent Citations
Polyacrylic acid and sodium lignin sulfonate composite binder for silicon-based negative electrode of lithium ion battery as well as preparation method and application of polyacrylic acid and sodium lignin sulfonate composite binder
CN116804138A
Lithium ion battery negative electrode binder and preparation method and application thereof
CN117757425A
Negative electrode binder for lithium-ion secondary battery
JP2022119352A
Mussel-inspired tissue adhesives and methods of use thereof
WO2024040270A2
Cited By
Carboxymethyl cellulose derivative as well as preparation method and application thereof
CN119874944A